Structural lightweight concrete production by using oil palm shell - Sobuz, Habibur Rahman; Md. Sadiqul Hasan, Noor; Tamanna, Nafisa; Islam, Md. Saiful (Hindawi Publishing Corporation, 2014)
Conventional building materials are widely used in a developing country like Malaysia. This type of material is costly. Oil palm shell (OPS) is a type of farming solid waste in the tropical region. This paper aims to investigate strength characteristics and cost analysis of concrete produced using the gradation of OPS 0–50% on conventional coarse aggregate with the mix proportions 1 : 1.65 : 2.45, 1 : 2.5 : 3.3, and 1 : 3.3 : 4.2 by the weight of ordinary Portland cement, river sand, crushed stone, and OPS as a substitution for coarse aggregate. The corresponding w/c ratios were used: 0.45, 0.6, and 0.75, respectively, for the defined mix proportions. Test results indicate that compressive strength of concrete decreased as the percentage of the OPS increased in each mix ratio. Other properties of OPS concrete, namely, modulus of rupture, modulus of elasticity, splitting tensile strength, and density, were also determined and compared to the corresponding properties of conventional concrete. Economic analysis also indicates possible cost reduction of up to 15% due to the use of OPS as coarse aggregate. Finally, it is concluded that the use of OPS has great potential in the production of structural lightweight concrete.